Molecular docking of several compounds in katuk (Sauropus androgynus (L.)) leaves as anti-breast cancer in AKT1 protein - Sutjiningsih, Ni Nyoman Ota; Ulisya, Azzaima Ayu; Utami, Amalda; Natalia, Christine; Mumtaz, Fakhira Chairunnisa; Yulanda, Nola Rohmi Eka; Sari, Victoria Rekina; Auli, Winni Nur; Saputro, Anjar Hermadi (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2024)
Breast cancer represents a leading cause of cancer-related mortality among women worldwide. Katuk leaves (Sauropus androgynus L.) demonstrate potential as anticancer agents through their ability to inhibit metastatic processes. The AKT1 protein plays a critical role in preventing apoptosis in breast cancer cells, making it an important therapeutic target. This study employed molecular docking analysis to evaluate the binding affinity of bioactive compounds from katuk leaves to the AKT1 protein. The docking methodology involved protein preparation using structures obtained from the Protein Data Bank (PDB ID 3O96), followed by ligand preparation and validation using AutoDockTools version 1.5.6. Chemical interaction analysis was performed using BIOVIA Discovery Studio 2021 software. The binding energy analysis encompassed one native ligand, one reference drug (afuresertib), and five katuk-derived compounds: kaempferol, catechin, coumarin, squalene, and phytol. The respective binding energies were determined as -12.59, -8.70, -5.92, -6.44, -5.05, -8.11, and -6.70 kcal/mol. Among the tested compounds, squalene exhibited the strongest binding affinity (-8.11 kcal/mol), demonstrating superior interaction with the AKT1 protein compared to other katuk-derived bioactive compounds. The in silico screening results indicate that bioactive constituents in katuk leaves possess favorable binding characteristics for breast cancer protein targets, with squalene showing particular promise as a natural AKT1 inhibitor.